2019
DOI: 10.3389/fbioe.2019.00087
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage-Driven Biomaterial Degradation Depends on Scaffold Microarchitecture

Abstract: In situ tissue engineering is a technology in which non-cellular biomaterial scaffolds are implanted in order to induce local regeneration of replaced or damaged tissues. Degradable synthetic electrospun scaffolds are a versatile and promising class of biomaterials for various in situ tissue engineering applications, such as cardiovascular replacements. Functional in situ tissue regeneration depends on the balance between endogenous neo-tissue formation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 98 publications
(75 citation statements)
references
References 67 publications
(91 reference statements)
1
74
0
Order By: Relevance
“…This outside‐interior remodeling style emphasized central role of PCL nanofibrous interface, in mediating profound PVAT‐biomaterial interaction that leads to myogenic differentiation. Although physical structures, such as fiber diameter or fiber density influences M2 transition of macrophages, [ 45 ] both in vitro and in vivo results in this study revealed DTβ4 incorporation is determinant to M1/M2 ratio conversion. For the first time, we found that DTβ4 treated macrophages presented more autophagosomes, indicating enhanced autophagy of cells.…”
Section: Discussionmentioning
confidence: 86%
“…This outside‐interior remodeling style emphasized central role of PCL nanofibrous interface, in mediating profound PVAT‐biomaterial interaction that leads to myogenic differentiation. Although physical structures, such as fiber diameter or fiber density influences M2 transition of macrophages, [ 45 ] both in vitro and in vivo results in this study revealed DTβ4 incorporation is determinant to M1/M2 ratio conversion. For the first time, we found that DTβ4 treated macrophages presented more autophagosomes, indicating enhanced autophagy of cells.…”
Section: Discussionmentioning
confidence: 86%
“…Interestingly, nanofiber cues compared to micro-fiber cues have particular potential to alter fibroblast response from repair to healing [25]. Furthermore, it has been demonstrated that different inflammatory responses were elicited depending on biomaterial grating patterns or electrospun fibers of different thickness and compositions [50][51][52]. While the description of the underlying links between inflammatory mechanisms and tendon homeostasis is thus crucial to understand the factors that drive tissue repair quality [53], these links have been under-investigated.…”
Section: Discussionmentioning
confidence: 99%
“…1,54 Via paracrine signaling, M2 macrophages have been shown to stimulate fibroblast proliferation and subsequent collagen deposition, while a more pro-inflammatory M1 macrophage profile augments the tissue degradative potential. 5,14,[55][56][57] We assessed the paracrine effects of our dynamically cultured macrophages on scaffold-seeded (myo)fibroblasts and observed minor differences in the proliferation or number of (myo)fibroblasts between the experimental groups (see ESI Fig. S6 †).…”
Section: Mechanically Conditioned Macrophages Distinctly Regulate (Mymentioning
confidence: 99%